Acute Sprint Interval Exercise Increases Both Cognitive Functions and Peripheral Neurotrophic Factors in Humans: The Possible Involvement of Lactate - Kujach, Sylwester; Olek, Robert Antoni; Byun, Kyeongho; Suwabe, Kazuya; Sitek, Emilia J.; Ziemann, Ewa; Laskowski, Radosław; Soya, Hideaki (Frontiers in Neuroscience, 2020)
There is increasing attention to sprint interval exercise (SIE) training as a time-efficient exercise regime. Recent studies, including our own (Kujach et al., 2018), have shown that acute high-intensity intermittent exercise can improve cognitive function; however, the neurobiological mechanisms underlying the effect still remain unknown. We thus examined the effects of acute SIE on cognitive function by monitoring the peripheral levels of growth and neurotrophic factors as well as blood lactate as potential mechanisms. Thirty-six young males participated in the current study and were divided into two groups: SIE (n=20; mean age: 21.0 ± 0.9 years) and resting control (CTR) (n=16; mean age: 21.0 ± 1.7 years). The SIE session consisted of five minutes of warm-up exercise and six sets of 30 s of all-out cycling exercise followed by 4.5 min of rest on a cycling-ergometer. Blood samples to evaluate the changes of serum concentrations of brain-derived neurotrophic factor (BDNF), insulin-like growth factor-1 (IGF-1), vascular endothelial growth factor (VEGF), and blood lactate (LA) were obtained at 3 time points: before, immediately after and 60 min after each session. A Stroop task and Trail Making Test (TMT) parts A and B were used to assess cognitive functions. Acute SIE shortened response times for both the Stroop task and TMT A and B. Meanwhile, the peripheral levels of BDNF, IGF-1, and VEGF were significantly increased after an acute bout of SIE compared to those in CTR. In response to acute SIE, blood lactate levels significantly increased and correlated with increased levels of BDNF, IGF-1, and VEGF. Furthermore, cognitive function and BDNF are found to be correlated. The current results suggest that SIE could have beneficial effects on cognitive functions with increased neuroprotective factors along with peripheral lactate concentration in humans.